2017
DOI: 10.1002/anie.201705014
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Microtesla SABRE Enhancement of 15N NMR Signals

Abstract: The hyperpolarization of heteronuclei via Signal Amplification by Reversible Exchange (SABRE) was investigated under conditions of heterogeneous catalysis and microtesla magnetic fields. Immobilization of [IrCl(COD)(IMes)], [IMes = 1,3-bis(2,4,6-trimethylphenyl), imidazole-2-ylidene; COD = cyclooctadiene] catalyst onto silica particles modified with NH2(CH2)3- linkers engenders an effective heterogeneous SABRE (HET-SABRE) catalyst that was used to demonstrate ~102-fold enhancement of 15N NMR signals in pyridin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 62 publications
3
58
0
3
Order By: Relevance
“…After pH 2 bubbling inside a magnetic shield, ~100-fold 15 N NMR enhancements (at 9.4 T) were obtained for 15 N-pyridine via SABRE-SHEATH—the first demonstration of SABRE enhancement of heteronuclei under heterogeneous conditions. [99] Finally, using an approach based on phase-transfer catalysis, Iali et al have demonstrated separation of HP agents (with P H up to ~10%) from organic solvents containing the homogeneous catalyst via agent partitioning into an immiscible aqueous phase. [100] While the polarization levels that were achieved with heterogeneous catalysis so far are too low for a biomedical application, the separation of catalyst and substrate is key and likely necessary to bring this emerging technology from benchtop to bedside.…”
Section: How To Make It Work: the Hyperpolarizer And Chemistry Of mentioning
confidence: 99%
“…After pH 2 bubbling inside a magnetic shield, ~100-fold 15 N NMR enhancements (at 9.4 T) were obtained for 15 N-pyridine via SABRE-SHEATH—the first demonstration of SABRE enhancement of heteronuclei under heterogeneous conditions. [99] Finally, using an approach based on phase-transfer catalysis, Iali et al have demonstrated separation of HP agents (with P H up to ~10%) from organic solvents containing the homogeneous catalyst via agent partitioning into an immiscible aqueous phase. [100] While the polarization levels that were achieved with heterogeneous catalysis so far are too low for a biomedical application, the separation of catalyst and substrate is key and likely necessary to bring this emerging technology from benchtop to bedside.…”
Section: How To Make It Work: the Hyperpolarizer And Chemistry Of mentioning
confidence: 99%
“…[49] Moreover,w eh ave recently reported the preparation of pure (i.e.,c atalyst-free) HP metronidazole solutions [36] as well as heterogeneous 15 NS ABRE-SHEATH [50] and 15 NS ABRE-SHEATH HP metronidazole in aqueous media, [51] thereby potentially enabling the preparation of biologically compatible HP MNZ-15 N 3 injectable formulation(s). [49] Moreover,w eh ave recently reported the preparation of pure (i.e.,c atalyst-free) HP metronidazole solutions [36] as well as heterogeneous 15 NS ABRE-SHEATH [50] and 15 NS ABRE-SHEATH HP metronidazole in aqueous media, [51] thereby potentially enabling the preparation of biologically compatible HP MNZ-15 N 3 injectable formulation(s).…”
Section: Spin-relayed Polarization Transfermentioning
confidence: 99%
“…Heterogeneous catalysis has been widely applied in PHIP and DNP methods previously. [73] Currently,n either heterogeneous SABRE nor aqueous SABRE delivers polarization levels that are commensurate with biomedical imaging. [72] This enhancement, despite being low,w as shown to be achieved only from the heterogeneous catalysis by comparison to control experiments on the supernatant solution.…”
Section: Heterogeneous Sabrementioning
confidence: 99%